2022
DOI: 10.3390/nu14193947
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation and Allergic Diseases during Childhood: A Systematic Review and Meta-Analysis

Abstract: We performed a systematic review and meta-analysis to investigate the effects of vitamin D (VitD) supplementation on children with allergic diseases. MEDLINE, Embase, Web of Science, the Cochrane library, and three Chinese databases were searched up to 15 August 2022. Randomized controlled trials (RCTs) comparing a VitD supplementation versus a placebo for children with allergic diseases were included. Thirty-two RCTs with 2347 participants were included. VitD supplementation did not reduce the risk of asthma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 65 publications
0
21
0
1
Order By: Relevance
“…These inconsistent conclusions of asthma exacerbation may be attributed to the variations in serum 25(OH)D concentrations among asthmatic children. Two of the included reviewsF I G U R E 1 PRISMA flow diagram.found that vitamin D supplementation significantly reduced the risk of asthma exacerbations only in the subgroup population whose serum 25(OH)D levels were low (<10 ng/mL for one review and <25 nmol/L for the other review) 18,19. Besides, while microbial supplementation has been extensively studied in the paediatric context, our analyses revealed negligible effects on children.A shift in the key intervention approaches has been observed from supplements and diet in the prenatal and infancy stages to exercise and weight management in the childhood stage.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…These inconsistent conclusions of asthma exacerbation may be attributed to the variations in serum 25(OH)D concentrations among asthmatic children. Two of the included reviewsF I G U R E 1 PRISMA flow diagram.found that vitamin D supplementation significantly reduced the risk of asthma exacerbations only in the subgroup population whose serum 25(OH)D levels were low (<10 ng/mL for one review and <25 nmol/L for the other review) 18,19. Besides, while microbial supplementation has been extensively studied in the paediatric context, our analyses revealed negligible effects on children.A shift in the key intervention approaches has been observed from supplements and diet in the prenatal and infancy stages to exercise and weight management in the childhood stage.…”
mentioning
confidence: 70%
“…These inconsistent conclusions of asthma exacerbation may be attributed to the variations in serum 25(OH)D concentrations among asthmatic children. Two of the included reviews found that vitamin D supplementation significantly reduced the risk of asthma exacerbations only in the subgroup population whose serum 25(OH)D levels were low (<10 ng/mL for one review and <25 nmol/L for the other review) 18,19 …”
Section: Resultsmentioning
confidence: 99%
“…Vitamin D 3 deficiency is a risk factor for allergic diseases, especially in children (19). A study has shown that vitamin D 3 supplements can reduce the severity of atopic dermatitis and AR in children (20). Through animal experiments, some scholars have revealed that vitamin D 3 has a preventive and therapeutic effect on AR, which provides theoretical guidance for practical application (21).…”
Section: Discussionmentioning
confidence: 99%
“…10 At present, research results have confirmed that the serum vitamin D levels of obese patients are significantly lower than those of normal weight individuals, 11 and the vitamin D levels of AD patients are also lower than those of healthy individuals. [12][13][14] Therefore, we hypothesized that vitamin D may play some roles in the relationship between obesity and AD. This study analyzed vitamin D levels in AD patients of different body mass index (BMI) classification and their correlation with Severity Scoring of Atopic Dermatitis (SCORAD), total immunoglobulin E (tIgE), and EOS, also provided important evidence for the involvement of vitamin D in the pathogenesis of overweight/obesity AD.…”
Section: Introductionmentioning
confidence: 99%